2006
DOI: 10.1016/j.atmosenv.2006.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling residential exposure to secondhand tobacco smoke

Abstract: We apply a simulation model to explore the effect of a house's multicompartment character on a nonsmoker's inhalation exposure to secondhand tobacco smoke (SHS). The model tracks the minute-by-minute movement of people and pollutants among multiple zones of a residence and generates SHS pollutant profiles for each room in response to room-specific smoking patterns. In applying the model, we consider SHS emissions of airborne particles, nicotine, and carbon monoxide in two hypothetical houses, one with a typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 39 publications
2
46
0
2
Order By: Relevance
“…The mean estimated ETS-PM concentration of 16 mg/m 3 for exposed households in our study falls on the lower side of the range of concentrations measured in previous large-scale residential ETS studies (Dockery and Spengler, 1981;Leaderer, 1990;Ozkaynak et al, 1996). Our results are also in agreement with recent modeling studies: Klepeis et al reported means ranging from 6.6-49 mg/m 3 from multiple simulations using a simple box model approach; and Myatt et al reported a mean of 15 mg/m 3 and a median of 17.8 mg/m 3 using the CONTAM model (Klepeis and Nazaroff, 2006;Myatt et al, 2008). These studies incorporated time-activity patterns and ventilation patterns but relied on a hypothetical smoking population, whereas our study is a snapshot characterization of equilibrium concentrations based on parameters estimated from a national survey.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The mean estimated ETS-PM concentration of 16 mg/m 3 for exposed households in our study falls on the lower side of the range of concentrations measured in previous large-scale residential ETS studies (Dockery and Spengler, 1981;Leaderer, 1990;Ozkaynak et al, 1996). Our results are also in agreement with recent modeling studies: Klepeis et al reported means ranging from 6.6-49 mg/m 3 from multiple simulations using a simple box model approach; and Myatt et al reported a mean of 15 mg/m 3 and a median of 17.8 mg/m 3 using the CONTAM model (Klepeis and Nazaroff, 2006;Myatt et al, 2008). These studies incorporated time-activity patterns and ventilation patterns but relied on a hypothetical smoking population, whereas our study is a snapshot characterization of equilibrium concentrations based on parameters estimated from a national survey.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we assumed that our study population spends one half of its waking time inside home, and multiplied the predicted daily number of cigarettes by a factor of 0.5 to obtain the predicted daily number of cigarettes smoked at home (Table 1b). We assumed a constant rate of smoking; although it is possible that more cigarettes are smoked outside of working hours given the increasing smoking restrictions in public places, no information was available on this and we chose to use a linear rate based on previous literature (Klepeis and Nazaroff, 2006).…”
Section: Ahs Smoking Predictionsmentioning
confidence: 99%
See 3 more Smart Citations